2015
DOI: 10.1159/000446253
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Threshold for Blood Transfusion in a Pediatric Intensive Care Unit

Abstract: Objective: To evaluate the hemoglobin threshold for red cell transfusion in children admitted to a pediatric intensive care unit (PICU). Methods: Retrospective chart review study. Tertiary care PICU. Critically ill pediatric patients requiring blood transfusion. No intervention. Results: We analyzed the charts of all children between 1 month and 21 years of age who received packed red blood cell (PRBC) transfusions during a 2-year period. The target patients were identified from our blood bank database. For an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A previous study revealed the same result (OR 5.03; CI95%: 1.77–14.35) [ 10 ]. Bacteremia is the presence of pathogenic bacteria in circulation that has been found to have a significant relationship with mortality and morbidity in children [ 23 ]. Bacteremia has also been used to predict the presence of pneumonia caused by bacterial infection, which frequently had more severe clinical manifestations and complications [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed the same result (OR 5.03; CI95%: 1.77–14.35) [ 10 ]. Bacteremia is the presence of pathogenic bacteria in circulation that has been found to have a significant relationship with mortality and morbidity in children [ 23 ]. Bacteremia has also been used to predict the presence of pneumonia caused by bacterial infection, which frequently had more severe clinical manifestations and complications [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We defined anemia based on laboratory results and the 2011 WHO recommendation for anemia diagnosis. Children were categorized as having anemia and non-anemia based on their age [ 9 ]. Cerebral edema was a condition of cerebral edema in patients that can be seen from the computerized tomography (CT) scan image and stated in the medical records [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The stable group included the patients who did not meet the criteria mentioned earlier. In a previous study, hemoglobin threshold for blood transfusion requirements was studied using similar groups [ 6 ]. Each patient’s demographics variables, pre- and post-platelet transfusion clinical variables and mortality were recorded.…”
Section: Methodsmentioning
confidence: 99%